Let us explain everything: pupils’ perspectives of the affordances of mobile technology during primary science inquiry - Blackmore, Karen; Rønningsbakk, Lisbet (Frontiers in Education, 2023)
This three-year longitudinal case study focused on the deployment of mobile technology in the form of tablet computers (iPads), during Inquiry Based Science Education (IBSE). The research took place in a larger than average primary school in the West Midlands, U.K., which showed a strong commitment to Technology Enhanced Learning (TEL) resulting in iPads being used as an integral learning tool, across the entire curriculum. During the research, pupils in Upper Key Stage Two (10-11 year olds) were observed taking part in science weeks which consisted of intense periods of science inquiry, much of which was child-led. The impact of the embedded use of iPads was monitored by scrutinising pupils’ work in the form of multimedia presentations and experimental reports. Pupils’ learning behaviours and attitudes to mobile technology were explored through observations and paired interviews. The embedded use of iPads during IBSE was shown to increase science knowledge acquisition and support scientific literacy, recording of processes and aid understanding of working scientifically. Furthermore, iPads were shown to afford opportunities for personalisation of scientific learning experiences and foster collaboration at several levels, factors which were highly valued by the pupils. The outcomes of this study can be used to further inform the refinement of m-learning strategies in primary science and illuminate opportunities for developing the practice of science pedagogues.